2022
DOI: 10.1007/s10840-022-01314-w
|View full text |Cite
|
Sign up to set email alerts
|

Role of empirical isolation of the superior vena cava in patients with recurrence of atrial fibrillation after pulmonary vein isolation—a multi-center analysis

Abstract: Background Non-pulmonary vein (PV) triggers play a role in the initiation of atrial fibrillation (AF), with the superior vena cava (SVC) being a common location. The aim of the current study was to investigate a strategy of empirical SVC isolation (SVCI) in addition to re-isolation of PV in patients with recurrence of AF after index PV isolation (PVI). Methods We retrospectively analyzed consecutive patients from two centers with recurrence of AF after ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Non-pulmonary vein triggers play a role in the initiation of atrial fibrillation [1,2]. In our case, when the Pentaray electrode was sent to the superior vena cava, the arrhythmia should have been atrial fibrillation for the completely unequal AA interval, and the various potential amplitudes and the potential period should have been less than 250 ms.…”
Section: Discussionmentioning
confidence: 71%
“…Non-pulmonary vein triggers play a role in the initiation of atrial fibrillation [1,2]. In our case, when the Pentaray electrode was sent to the superior vena cava, the arrhythmia should have been atrial fibrillation for the completely unequal AA interval, and the various potential amplitudes and the potential period should have been less than 250 ms.…”
Section: Discussionmentioning
confidence: 71%
“…Knecht et al compared empiric circumferential SVCI in addition to PVI (if the number of reconnected PVs during redo ablation procedure were ≤1) and found that empiric SVCI does not confer any advantage as far AF recurrences are concerned [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…For patients with persistent forms of AF, it is more likely to have non-PV triggers, such as the left atrial posterior free wall [ 18 , 19 , 20 ], the left atrial appendage [ 21 ], the superior vena cava (young patients with AF had a higher incidence of only non-PV foci, mostly located here) [ 22 , 23 , 24 , 25 ], the coronary sinus [ 26 , 27 ], and the ligament of Marshall [ 28 , 29 ]. For non-PV foci patients, the isolation of them was a significant factor affecting the achievement of better clinical outcomes following AF ablation [ 30 ].…”
Section: Pathophysiology Of Atrial Fibrillationmentioning
confidence: 99%